STUDI TENTANG DESAIN MOTIF DAN TEKNIK BATIK TANAH LIEK DI SANGGAR CITRA MONALISA SAWAHAN PADANG - M. ARSSAD, Dra. Jupriani, M.Sn, Drs. Erwin, M.Sn (Universitas Negeri Padang, 2015)
Batik Tanah Liek is a batik that become a characteristic of Minangkabau. This batik has different on coloring process which use clayey. This research purposed to describe the motif design and technique on the Batik Tanah Liek on the Sanggar Citra Monalisa in Sawahan, Padang. The reaserch method that used is qualitative research with approach descriptive. The type of data that’s used is a primary data was obtained from the craftsman, head of Sanggar Citra Monalisa, head of Promotion and Cooperation Department, Head of culture and tourism Padang city and secondary data obtained from the study of librarianship. Data collected through observation, interview and documentation.Key Words: Design Motifs, Techniques Of Batik, Batik Tanah Liek